Economic statecraft in China’s New Overseas Special Economic Zones: Soft power, business, or resource security? - Bräutigam, Deborah; Tang, Xiaoyang (International Food Policy Research Institute, 2012)
China’s growing economic engagement with other developing countries has aroused heated debates. Yet there has been relatively little research on when, how, and why the Chinese state intervenes in the overseas economic activities of its firms. We examine China’s program to establish overseas special economic zones as one tool of Beijing’s economic statecraft. We trace the process by which they were established and implemented, and we investigate the characteristics of the 19 initial zones. China’s state-sponsored economic diplomacy in other developing countries could play three major strategic roles: strengthening resource security, enhancing political relationships and soft power, and boosting commercial opportunities for national firms. We conclude that even in countries rich in natural resources, the overseas zones are overwhelmingly positioned as commercial projects and represent a clear case of the international projection of China’s developmental state. In Africa (but not generally elsewhere), they also enhance China’s soft power.